Evaluation of the biobutanol production from two agroindustrial wastes generated in the coffee growing region: plantain peel and milk whey (2017)
The need to replace fossil fuels has led to the search for new alternatives to reduce the pollution generated. Butanol is a biofuel that has great advantages over others more studied like ethanol. Additionally, it allows the approach of a platform under the concept of biorefinery to obtain added-value products. On the other hand, the inadequate disposal of the majority of agro-industrial and industrial waste generates great contamination. For that reason, it is necessary to find an adequate use for them. That is why this thesis presents the experimental evaluation of the production of butanol from plantain peel and milk whey, using the strain Clostridium acetobutylicum ATCC 824, as well as the technical, economic and environmental evaluation of a chemical platform for obtaining butyl acetate, butyl acrylate and butyl propionate from the butanol obtained in the fermentations. The results show that it is possible to obtain butanol from both residues. However, the milk whey is a raw material for the process that must be carried out only at high scale, since it does not present the same yields of sugar as the plantain peel, obtaining lower butanol flows and, therefore, value-added products, making the process economically unviable (Texto tomado de la fuente)